Pemanfaatan sumber nitrogen organik dalam pembuatan nata de coco - Budi Santosa; Rozana Rozana; Astutik Astutik (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Nata de coco is made from raw coconut water which is fermented using the Acetobacter xylinum bacteria. This product has the characteristics of a white color, a thickness of approximately 1-2 cm and a chewy texture like a gel. The largest content in nata de coco is fiber known as bacterial cellulose. In addition to requiring sugar as a carbon source, making nata de coco also requires a source of nitrogen to activate the extracellular enzymes of the Acetobacter xylinum bacteria in the manufacture of nata cellulose. Sources of nitogen used in the manufacture of nata de coco generally use inorganic nitrogen sources, which in their development have caused many pros and cons, especially with regard to food safety issues when this product is consumed as a beverage. This study aims to obtain the best alternative nitrogen source and concentration in making nata de coco. The experimental design used in this study was nested randomized design with 2 factors as the first factor, the type of nitrogen source, while the second factor was the concentration of the nitrogen source in the first factor. The types of nitrogen sources used as the first factor were tofu industrial wastewater, green bean sprouts and Azolla microphylla, while the second factor was the concentration of nitrogen sources consisting of 4 levels, namely 0.5%, 1%, 1.5% and 2%. The parameters observed in this study were thickness of nata de coco, weight of nata de coco, crude fiber of nata de coco, number of Acetobacter xylinum cells in the nata de coco layer. The results showed that organic nitrogen sources (tofu, sprouts and Azolla microphylla liquid waste can be an alternative substitute for inorganic nitrogen sources (urea, ZA and ammonium sulfate) which have been commonly used in making nata. The highest quality nata de coco is produced from the treatment of organic nitrogen sources. sprouts with a concentration of 1.5% with a thickness of 2.83 cm, a weight of 279.33 grams, a crude fiber content of 4.14% and the number of Acetobacter xylinum cells in the cellulose layer 0.4 x 107 cells / ml.